Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.21767/2254-9137.100041
|View full text |Cite
|
Sign up to set email alerts
|

Public Health, Mental Health and Primary Care Differences in Urban and Rural Counties in a System of Care for Children with Special Healthcare Needs

Abstract: Background: Collaboration among partners in a health system of care (SOC) has many benefits. In large and complex systems, the role of public health, mental health, and primary care play critical roles in the provision of care. How these systems vary across urban and rural settings is understudied. Understanding of perceived roles and ongoing collaboration across these sectors in urban and rural communities is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Unmet need for dental care and mental health services are the most frequently reported. Other studies have demonstrated that these two vital services are difficult to obtain [8,9]. Having an unmet need is consistently associated with lower family income and lack of continuous insurance coverage.…”
mentioning
confidence: 99%
“…Unmet need for dental care and mental health services are the most frequently reported. Other studies have demonstrated that these two vital services are difficult to obtain [8,9]. Having an unmet need is consistently associated with lower family income and lack of continuous insurance coverage.…”
mentioning
confidence: 99%